COMPREHENSIVE ASSESSMENT ROADSIDE INJURIES THROUGH HIGH-RESOLUTION THREE-DIMENSIONAL LASER SCANNING (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Roadside injuries are a significant concern within transportation infrastructure, necessitating effective monitoring and assessment methodologies. In this study, we introduce a novel approach for evaluating roadside injuries using high-resolution three-dimensional laser scanning systems. Through a meticulous selection process based on road cover characteristics, we implement a localized roadside monitoring methodology. The aim is to accurately identify and assess injuries, leveraging the precise data captured by laser scanning systems. By analyzing this data, we seek to provide practical insights for informing future road surface restoration activities. This research contributes to enhancing the efficiency and precision of roadside injury evaluation, ultimately facilitating improved maintenance and safety measures within transportation networks.
Keywords: GNSS; IMU; LiDAR; TIN; RINEX; CHCNAV